Rekayasa Wrist Rest Menggunakan Swivel Joint untuk Mengurangi Risiko CTS - Zefanya, Kristian; Guspara, Winta Adhitia; Nur, Christmastuti (Universitas Dinamika, 2025)
In the era of information and communication technology, keyboards are part of the work carried out via computers. The keyboard is the primary component in carrying out commands for the computer. High intensity use of keyboards and computers can change body position for the worse, and cause new diseases, for example Carpal Tunnel Syndrome (CTS). CTS is a syndrome that is often caused by repetitive movements and poor body posture. In CTS, effective preventive solutions have not been effective. This research uses qualitative methods to examine the factors that cause CTS, as well as finding solutions through product design. The goal is to design keyboard products and supporting items that can provide a feeling of comfort, safety and prevent changes in posture. There are several stages in this research, including studying employee behavior with keyboard use, analyzing risk factors from the literature, and testing and user interviews regarding the new product from this research.